Kakiemon porcelain : a handbook - Fitski, Menno, 1967-; Keramiekmuseum Princessehof; Impey, Harriet (Leiden : Leiden University Press ; Amsterdam : Rijksmuseum, 2011)
The book provides a comprehensive overview of Japanese and European sources and collections, giving a fresh perspective on Kakiemon to anyone interested in studying pieces in collections worldwide. The book contains over 300 colour images, many from the extensive collection of the Rijksmuseum in Amsterdam, and offers a wealth of detail to illustrate stylistic points. 'Kakiemon porcelain. A handbook' presents all the practical tools necessary for the attribution and dating of Kakiemon porcelain. The Kakiemon style and characteristics are exhaustively analyzed against the background of trade and reception developments.0A must for Kakiemon collectors, professionals and enthusiasts alike, and for anyone interested in Japanese ceramics.
1. The trade in porcelain -- 2. Kakiemon in Europe -- 3. Kakiemon in Japan -- 4. A chronological overview -- 5. Kakiemon porcelain manufacture -- 6. Designs and motifs.
Published in connection with the exhibition "Kakiemon: Finest porcelain art from Japan"
Includes bibliographical references (pages 168-171) and index.
Keywords: Kakiemon porcelain -- Exhibitions; Porcelain, Japanese -- 1868- -- Exhibitions; Porcelain, Japanese -- Edo period, 1600-1868 -- Exhibitions